Personnel and human resource management - Schuler, Randall S. (St. Paul, MN West Pub. Co., 1987)
Contents: Personnel and human resource management; Human resource planning; Job analysis; Selection and placement...
Includes bibliographical references and indexes
Keywords: Quản trị kinh doanh